ADOLESCENT`S NON-VERBAL FEEDBACK ON A DIGITAL MESSAGE IN TEACHING - Kecman, Violeta R (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
In this article, non-verbal feedback is viewed as a non-verbal adolescents’ communication response to a communication stimulus in the form of a message sent through digital media as a didactic tool in teaching. The theoretical considerations cover the dimensions of non-verbal behavior and the semiotics of non-verbal communication in digital interpersonal media. The second half of the article presents an empirical research of an experimental character, conducted in the Fifth Belgrade Gymnasium with fourth grade students. The aim of the research is to identify a communication feed-back on information whose content implies critical potential, that is, which can encourage critical thinking of adolescents in the teaching process, lead to the identification of cause and effect relationships, and to draw conclusions from the given data. The methodological framework of empirical research is quantitative. Group interviews of informative nature and open-ended surveys were used. The results of the research were obtained by a comparative method, observing, comparing and analyzing the feed-back on a message that implies the potential for critical thinking, in relation to a message that does not imply analysis and synthesis abilities, but is based on information recognition and knowledge reproduction. It was concluded that if adolescents were given the opportunity to show a critical attitude, they would respond non-verbally in digital communication in teaching. When the message does not imply the potential for incitement to critical thinking, but for the recognition of known information and simple reproduction of data, the communicative reaction in teaching is always verbal.